Determination of Models of Simple Regression and Multivariate Analysis for the Forecast of the Electricity Price in Colombia at 2030 - Bueno, Nelson Javier Hernández; Calderón, MarÃa de los Ãngeles Pinto; Maldonado, Yecid Alfonso Muñoz; Castro, Adalberto Ospino (International Journal of Energy Economics and Policy, 2018)
The electricity price in Colombia responds to demographic, economic, climatic changes, among others, that generate uncertainty and therefore risks in the electric production. Considering that the decision-making process has a great importance in the electricity market and that the participation of generators in energy auctions is usually based on intuition and previous experience, the need to study the possible alternatives and methods that minimize the risks before deciding some important matter can be appreciate. In this article, the estimation of the behavior of electrical energy prices in Colombia at the year 2030 for different scenarios and there are propose the following scientific models: (i) Simple regression; (ii) Econometric model. As result are obtained forecasts for each model, identifying that the econometric model has the lowest margin of error compared to the historical data that considers the behavior of different variables for the forecast. Keywords: Econometric Modeling, methods of statistical simulation, forecasting, electricity price. JEL Classifications: C13, C15, Q47